Diabetes in COVID‐19 pandemic‐prevalence, patient characteristics and adverse outcomes. Issue 7 (14th March 2021) - Abdelhafiz, Ahmed H.; Emmerton, Demelza; Sinclair, Alan J.
Abstract: Background: Current literature on COVID‐19 pandemic has identified diabetes as a common comorbidity in patients affected. However, the evidence that diabetes increases the risk of infection, effect of diabetes on outcomes and characteristics of patients at risk is not clear. Objectives: To explore the prevalence of diabetes in COVID‐19 pandemic, effect of diabetes on clinical outcomes and to characterise the patients with diabetes affected by COVID‐19. Methods: A literature review of articles published in English language and reported outcomes on prevalence and effect of diabetes on outcomes and patients' characteristics. Results: The prevalence of diabetes in COVID‐19 patients appears similar to that in the general population. The evidence of diabetes increasing the risk of severe infection and adverse outcomes is substantial. The progression of the disease into acute respiratory distress syndrome, the requirement for intensive care admission or mechanical ventilation and mortality all have been increased by the presence of diabetes. Patients with diabetes at risk of COVID‐19 appear to be obese, of older age, have uncontrolled glycaemia and have coexisting comorbidities especially cardiovascular disease and hypertension. Tight glycaemic control on admission to hospital using insulin infusion has shown some beneficial effects; however, the role of hypoglycaemic medications in the management of these patients is not yet clear. Conclusion: High risk group should be identified and prioritised in future vaccination programmes. Future research is required to optimise management of patients with diabetes and develop new ways to manage them via technological developments such as telecare.